2017
DOI: 10.1038/pr.2017.143
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in urea cycle enzyme genes are associated with persistent pulmonary hypertension of the newborn

Abstract: BackgroundPersistent pulmonary hypertension of the newborn (PPHN) is characterized by elevated pulmonary vascular resistance. Endogenous nitric oxide is critical for regulation of pulmonary vascular resistance. Nitric oxide is generated from L-arginine, supplied by the urea cycle (UC). We hypothesized that polymorphisms in UC enzyme genes and low concentrations of UC intermediates are associated with PPHN.MethodsWe performed a family-based candidate gene analysis to study 48 single-nucleotide polymorphisms (SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 34 publications
(37 reference statements)
0
24
0
1
Order By: Relevance
“…NO, a critical factor in cell growth and vasodilation has been well profiled in the pathogenesis of PAH [ 21 23 ]. The substrate of NO is arginine, which is mainly supplied by the urea cycle, is a linkage of the urea cycle to PAH [ 24 ]. NOS converts arginine to citrulline while simultaneously producing NO and water [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…NO, a critical factor in cell growth and vasodilation has been well profiled in the pathogenesis of PAH [ 21 23 ]. The substrate of NO is arginine, which is mainly supplied by the urea cycle, is a linkage of the urea cycle to PAH [ 24 ]. NOS converts arginine to citrulline while simultaneously producing NO and water [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“… 33 NO is generated from L-arginine, supplied by the urea cycle. 34 Arginine is regulated by ASS1 and CPS1, and thus the loss of ASS1 and CPS1 might lead to reduction of NO. It is suggested that overexpression of NO in tumor tissues induces tumor cell toxicity and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found three variants in CPS1 , one in a homozygous state, a gene for which neonatal susceptibility to PAH has been suggested with an increase of pulmonary arterial pressure after a surgical repair of congenital heart defects [ 37 ]. Furthermore, polymorphisms in CPS1 have also been related to persistent pulmonary hypertension of the newborn (PPHN) [ 38 ]. All variants were classified as VUS and unfortunately, no parental samples were available for segregation analysis.…”
Section: Discussionmentioning
confidence: 99%